Sources of cigarettes for youth smokers in Malaysia: findings from the National Health and Morbidity Survey (NHMS) 2022: Adolescents Health Survey (AHS) - Lim, Kuang Hock; Cheong, Yoon Ling; Lim, Kuang Kuay; Lim, Jia Hui; Abdul Hamid, Hamizatul Akmal; Riyadzi, Mohd Ruhaizie; Ghazali, Sumarni Mohd; Kee, Chee Cheong; Yong Kang, Cheah; Shao Hui, Chong; Marine, Ali Aman; Mat Hashim, Mohd Hazilas; et al. (European Publishing, 2025)
INTRODUCTION Developing effective intervention programs to lower adolescent smoking requires a thorough understanding of the sources and methods of youth tobacco product acquisition. This study aimed to identify the sources of cigarettes and related variables among adolescent smokers in Malaysian schools using the latest national data from the National Health and Morbidity Survey: Adolescents Health (NHMS: AHS) 2022. METHODS We conducted the NHMS 2022: AHS to obtain a representative sample of school-age teenagers via a cross-sectional study design and a multi-stage sampling approach. We selected 1934 school-going adolescents aged 13–17 years who have smoked at least once in the previous 30 days from a total of 33523 respondents in the study. Data were collected from the participants using a pre-validated self-administered questionnaire. The analysis involved calculating adjusted odds ratios (AORs) with 95% confidence intervals (95% CIs). Furthermore, we examined potential two-way interactions between the independent variables. RESULTS The study found that 6.2% (95% CI: 5.9–6.6) of teenagers in schools are currently smoking, with a notably higher percentage of male to female current smokers (10.8% vs 1.6%). Approximately 23.1% of current smokers are frequent smokers. Almost three-quarters of current smokers obtained their cigarettes from fixed premises (38.9%), and that friends (34.9%) were the primary sources of cigarettes among adolescents. The data show that more than half (59.7%, 95% CI: 57.0–62.4) of current smokers obtained cigarettes from commercial sources. CONCLUSIONS The study found that a notably more significant proportion of adolescent smokers obtained their cigarettes from commercial vendors compared to their friends. These finding implies that increased law enforcement and health promotion programs are needed to lower the incidence of adolescent smoking in Malaysia.